O papel inclusivo do atendimento educacional especializado para os estudantes com deficiência na sala de recursos no município de Rondonópolis - MT - Bernacki, Juliane Rogonni Ferrari (2021)
Specialized Educational Assistance is a public policy that institutionalizes methodological devices for inclusion that have the function of identifying, elaborating and organizing pedagogical and accessibility resources, with a view to teaching learning and the elimination of institutional barriers that prevent full participation of students with disabilities , autism spectrum disorder, high skills and giftedness in the school space, according to the specifics and their educational needs. The objective of this research is to verify what type of inclusion is being offered through Specialized Educational Service (AEE) in the resource rooms of Rondonópolis, MT, for students with physical and sensory disabilities. This work uses a qualitative approach and documentary analysis, and the interview is a research instrument, carried out in a school in the municipal network. Semistructured interviews were conducted with teachers from AEE and the common room, principal, coordinator, parents or guardians of children with disabilities who participate in educational services and interns who work directly with students. In this perspective of verifying some important factors related to inclusion, the documents that are part of the school's constitution were also considered, such as the Political-Pedagogical Project (PPP), the Individual Development Plan (PDI), normative and others that were considered important to understand the inclusion process. This documentation is intended to elucidate the elements used in this research to verify the applicability and execution of public policies currently in force in the country. Theoretical contributions from authors of the critical theory of society were used, such as Theodor Adorno, Max Horkheimer, Crochík and others, who strive to elucidate the discussions about education for tolerance and coexistence, with actual inclusion. In order to problematize the reality described about Specialized Educational Assistance, it is necessary to ask a central question: what is the type of inclusion promoted by the ESA service in the municipality of RondonópolisMT and developed in the multifunctional resource rooms in order to promote inclusion in school spaces? and social? Thus, according to the results obtained by this research, it was found that the inclusive school, for it to happen, needs to reformulate curricula, assessments, teacher training and democratic educational policies, so that there is a transformation in the traditional school making it effectively inclusive.